Silage quality of six sorghum cultivars for sheep - Oliveira, Brena Santos; Pereira, Luiz Gustavo Ribeiro; Azevêdo, José Augusto Gomes; Rodrigues, José Avelino Santos; Velasco, Frederico Osório; Neves, André Luiz Alves; Maurício, Rogério Martins; Verneque, Rui da Silva; dos Santos, Rafael Dantas (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate the silage quality, fermentation profile, intake, and digestibility of six sorghum cultivars for sheep feeding. ’SF 15’, ’IPA 2502’, ’BRS 655’, ’BR 601’, ’BRS 506’, and ’Sudão’ were cultivated in randomized complete block designs with five replicates, harvested, and ensiled when plants reached the soft-dough grain stage. Silage quality was determined in laboratory silos. Intake and apparent digestibility were determined during 22 days, using 24 Santa Inês lambs (35.5±2.21 kg) randomly distributed in the treatments. Silage from ’IPA 2502’ had the lowest contents of dry matter, neutral detergent fiber, and acid detergent fiber; the highest nonfibrous carbohydrate and total digestible nutrient contents; and the greatest dry matter degradability. Silages from ’BR 601’ and ’BRS 506’ showed the highest values of crude protein, whereas those of ’SF 15’ and ’Sudão’ had the highest levels of fibrous fractions. Lambs fed silage from ’IPA 2502’ consumed more dry matter and nonfibrous carbohydrates, and their crude protein digestibility was also greater than that from the consumption of other cultivar silages. ’IPA 2502’ stands out for its nutritional characteristics, which resulted in better animal performance.